Clinicopathological Profile and Treatment Outcomes of Pediatric and Adolescent Non-Hodgkin’s Lymphoma Cases in a Tertiary Cancer Hospital of Central Nepal - Sharma, Krishna Sagar; Panthee, Sabita; Mehta, Subash (Journal of College of Medical Sciences-Nepal, 2025)
Background Non-Hodgkin’s lymphoma (NHL) is the most common type of lymphoma in pediatric and adolescent age groups. Advances in combination chemotherapy protocols have significantly improved survival, even in resource-limited countries. The objective of this study this study is to find the clinicopathological features and treatment outcomes of pediatric and adolescent NHL at B.P. Koirala Memorial Cancer Hospital (BPKMCH). Methods A retrospective cross-sectional study was conducted among 65 pediatric and adolescent patients diagnosed with NHL between 2008 and 2012. Clinical presentation, histopathology, staging, treatment received, and outcomes were analyzed. Chemotherapy regimens included CHOP/R-CHOP and MRC 842/841 protocols, with radiotherapy for selected patients were analyzed in this study. Results Among 65 patients, 72.3% were male. The most common age group was 13–19 years (53.8%). Cervical lymphadenopathy was the most frequent presentation (55.4%). Histologically, intermediate-grade lymphomas predominated (50%). The majority presented with stage III (41.5%) and stage IV (32.3%) disease. Of 60 patients treated, 45% (27/60) achieved cure, while 25% died before completion of therapy and 30% defaulted. Relapse occurred in 18% of cured patients. Only 22.2% of survivors remained on long-term follow-up. Conclusions Pediatric and adolescent non-Hodgkin’s lymphoma predominantly affects older children, with a male preponderance and frequent cervical lymphadenopathy. Most patients present with advanced-stage disease, and intermediate- and high-grade lymphomas are common. Treatment outcomes are variable, highlighting challenges such as relapse, treatment default, and poor follow-up. Early diagnosis and improved treatment adherence are essential to optimize outcomes in this population.